(untitled) (Research, Society and Development, 2022)
Objective: To identify reflections on the sexual and reproductive health of young people in the context of Primary Health Care. Method: The research was carried out through an integrative literature review, with a descriptive approach. The search was performed in the Virtual Health Library with the descriptors registered in the Health Sciences Descriptors: “adolescent”, “primary health care” and “sexual and reproductive health” and in PubMed Central with the descriptors of the Medical Subject Headings: “ adolescent”, “primary health care” and the keyword “sexual and reproductive health”, in both platforms the Boolean operator “AND” was used, resulting in 801 publications in the initial search. Full-text documents published in the last 5 years in Portuguese, English and Spanish were included. After reading, 14 scientific documents were selected, but 2 were excluded because they were duplicates. Data were analyzed and organized in a Microsoft Excel spreadsheet. Results: According to the findings, the evaluation of the services provided and the quality of care regarding sexual and reproductive health, the professionals’ view on the subject and accessibility were presented as the main perspectives of action in Primary Health Care for young people. Conclusion: Therefore, the sexual and reproductive health of adolescents is of particular relevance, given its feasible short- and long-term health outcomes.